Perceptions of organizational readiness for training and implementation of clinic-based community health workers. Issue 4 (24th June 2019) - Lee, Lily; Montgomery, Susanne; Gamboa-Maldonado, Thelma; Nelson, Anna; Belliard, Juan Carlos
Abstract : Purpose: The purpose of this paper is to assess perceptions of organizational readiness to integrate clinic-based community health workers (cCHWs) between traditional CHWs and potential cCHW employers and their staff in order to inform training and implementation models. Design/methodology/approach: A cross-sectional mixed-methods approach evaluated readiness to change perceptions of traditional CHWs and potential employers and their staff. Quantitative methods included a printed survey for CHWs and online surveys in Qualtrics for employers/staff. Data were analyzed using SPSS software. Qualitative data were collected via focus groups and key informant interviews. Data were analyzed with NVIVO 11 Plus software. Findings: CHWs and employers and staff were statistically different in their perceptions on appropriateness, management support and change efficacy ( p <0.0001, 0.0134 and 0.0020, respectively). Yet, their differences lay within the general range of agreement for cCHW integration (4=somewhat agree to 6=strongly agree). Three themes emerged from the interviews which provided greater insight into their differences and commonalities: perspectives on patient-centered care, organizational systems and scope of practice, and training, experiences and expectations. Originality/value: Community health workers serve to fill the gaps in the social and health care systems. They are an innovation as an emerging workforce in health care settings. Health care organizations need to learn how to integrate paraprofessionals such as cCHWs. Understanding readiness to adopt the integration of cCHWs into clinical settings will help prepare systems through trainings and adapting organizational processes that help build capacity for successful and sustainable integration.